2001
DOI: 10.1046/j.1471-4159.2001.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐derived neurotrophic factor (BDNF) mediates bone morphogenetic protein‐2 (BMP‐2) effects on cultured striatal neurones

Abstract: Bone morphogenetic proteins are members of the transforming growth factor-b superfamily that have multiple functions in the developing nervous system. One of them, bone morphogenetic protein-2 (BMP-2), promotes the differentiation of cultured striatal neurones, enhancing dendrite growth and calbindin-positive phenotype. Bone morphogenetic proteins have been implicated in cooperative interactions with other neurotrophic factors. Here we examined whether the effects of BMP-2 on cultured striatal neurones are med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 59 publications
1
17
1
Order By: Relevance
“…In contrast, studies by another group found that BMP treatment of cultured striatal cells increased the number of calbindinpositive interneurons, although this effect appeared to be an indirect one mediated by astrocytes and other growth factors (Gratacos et al, 2001(Gratacos et al, , 2002. In our study, null mutation of BMPR1a did not alter the total number of interneurons in the telencephalon, although there was a trend toward an increase.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, studies by another group found that BMP treatment of cultured striatal cells increased the number of calbindinpositive interneurons, although this effect appeared to be an indirect one mediated by astrocytes and other growth factors (Gratacos et al, 2001(Gratacos et al, , 2002. In our study, null mutation of BMPR1a did not alter the total number of interneurons in the telencephalon, although there was a trend toward an increase.…”
Section: Discussioncontrasting
confidence: 99%
“…Primary neurons from striatum were cultured from E18 CD-1 mice embryos as previously described (Gratacos et al, 2001). In brief, the dissected striatum was treated with 1.25% trypsin (Sigma-Aldrich) for 10 min before being mechanically dissociated with a flame polished Pasteur pipette.…”
Section: Methodsmentioning
confidence: 99%
“…However, BMP4 expression peaks in the cortex around the same time as BDNF, suggesting that BMP4 and BDNF might cooperate in the differentiation of the PV + interneurons in the cortex. Similar cooperative effects between BMPs and BDNF have been reported for other cell populations in the brain, and some of the effects of BMPs may have been mediated through BDNF (Galter et al, 1999;Gratacos et al, 2001). Unlike BDNF, little is known about the effects of BMP4 signaling on synaptic plasticity, or whether BMP4 expression is regulated by synaptic activity, although recently BMP signaling was implicated in enhancing synaptic plasticity in the hippocampus (Sun et al, 2007).…”
Section: Discussionmentioning
confidence: 67%